Large Beam Size Grating Coupler in Silicon-on-Insulator Using Fully Etched Subwavelength Gratings - Barona-Ruiz, Miguel; Moreno-Pozas, Laureano; Ginel-Moreno, Pablo; Ortega-Moñux, Alejandro; De-Oliva-Rubio, José; Molina-Fernández, Íñigo; Wanguemert-Pérez, Juan Gonzalo; Halir, Robert (Wiley, 2025)
Several emerging applications of silicon photonics, including sensing,ranging, and optical trapping, require ﬁxed, well-collimated beams that enableinteraction with targets placed centimeters away from the chip. Generatingsuch beams without using bulk-optic lenses entails radiating lightwaves withdiameters of hundreds of microns directly from the chip. Gratings withsuﬃciently low strength have so far only been shown in the silicon nitrideplatform using specialized shallow etch steps; in silicon-on-insulator theimplementation becomes much more challenging due to the increased indexcontrast. Here, the ﬁrst silicon-on-insulator grating capable of radiating suchlarge beams is reported. Using a fully etched, double-period subwavelengthstructure, with feature sizes compatible with deep-ultraviolet lithography, abeam diameter in excess of 350 𝛍m, with a 54% radiation eﬃciency, isexperimentally demonstrated.
Keywords: Fotónica; Silicio sobre aislante; Silicon-on-Insulator; Large Beam Size